Single photons from single CdSe quantum dot embedded in ZnSe nanowire. (22nd February 2010) - Aichele, T.; Sallen, G.; Tribu, A.; Andre, R.; Bougerol, C.; Tatarenko, S.; Kheng, K.; Poizat, J-Ph.
We report the growth of ZnSe nanowires and nanoneedles using molecular beam epitaxy (MBE). Different growth regimes were found, depending on growth temperature and the Zn-Se flux ratio. By employing a combined MBE growth of nanowires and nanoneedles without any postprocessing of the sample, we achieved an efficient suppression of stacking fault defects. This is confirmed by transmission electron microscopy and by photoluminescence studies. We have inserted a single CdSe quantum dot in these nanowires and we have observed strong photoluminescence from a single CdSe quantum dot embedded in a ZnSe nanowire. Exciton, biexciton and charged exciton lines have been identified unambiguously using photon correlation spectroscopy. This technique has provided a detailed picture of the dynamics of this new system. This type of semi-conducting quantum dot turns out to be a very efficient single photon source in the visible at a temperature as high as 220 K. Its particular growth technique opens new possibilities as compared to the usual self-asssembled quantum dots.